Glioma: Tryptophan Catabolite and Melatoninergic Pathways Link microRNA, 14-3- 3, Chromosome 4q35, Epigenetic Processes and other Glioma Biochemical Changes - V. Beischlag, Timothy; Anderson, George; Mazzoccoli, Gianluigi (Current Pharmaceutical Design, 2016)
Primary glioma, as well as secondary metastases, provide significant treatment challenges. An understanding of the biological underpinnings of glioma is likely to provide new pharmaceutical targets that will improve patient survival. Here, we look at the role that the kynurenine pathways and associated tyrptophan catabolites (TRYCATs) play in glioma, linking this to changes in oxidative and nitrosative stress (O), immuneinflammatory activity, the aryl hydrocarbon receptor (AhR), and the melatoninergic pathways. It is suggested that the interactions of O and the immune-inflammatory processes in glioma contribute to the induction of the TRYCATs via the kynurenine activation of the AhR, leading to increased indoleamine 2,3-dioxygenase, which deprives tryptophan for the necessary serotonin that is required as a precursor for the melatoninergic pathways. A diverse array of data pertaining to glioma can be linked to these pathways, including changes in miRNAs, epigenetic processes, estrogen receptors, 14-3-3, chromosome 4q35, neurotrophins, tristetraprolin and the N-acetylserotonin (NAS)/melatonin ratio. As many of these factors directly or indirectly act on the melatoninergic pathways, including variations in the NAS/melatonin ratio, it is suggested that the melatoninergic pathways may act as a hub that co-ordinate the multitude of changes occurring in glioma. Consequently, the melatoninergic pathways may be a significant pharmaceutical target for the treatment of this still very poorly managed condition.
Keywords: aryl hydrocarbon